2011
DOI: 10.1111/j.1349-7006.2010.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum and potent antitumor activities of YM155, a novel small‐molecule survivin suppressant, in a wide variety of human cancer cell lines and xenograft models

Abstract: Antitumor activities of YM155, a novel small-molecule survivin suppressant, were investigated in a wide variety of human cancer cell lines and xenograft models. YM155 inhibited the growth of 119 human cancer cell lines, with the greatest activity in lines derived from non-Hodgkin's lymphoma, hormone-refractory prostate cancer, ovarian cancer, sarcoma, non-small-cell lung cancer, breast cancer, leukemia and melanoma. The mean log growth inhibition of 50% (GI 50 ) value was 15 nM. The mean GI 50 values of YM155 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
155
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(168 citation statements)
references
References 36 publications
11
155
1
1
Order By: Relevance
“…65,66 Agents targeting survivin may provide encouragement for such treatments. The small-molecule YM155, which has shown promising growth inhibitory effects and potent antitumor activities in cell lines and xenograft models, 67,68 is the most well-studied survivin inhibitor. Although the drug's safety and tolerability have been confirmed, single-agent YM155, as monotherapy regimen, demonstrated only limited activity in patients with refractory diffuse large B-cell lymphoma in a phase II clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Agents targeting survivin may provide encouragement for such treatments. The small-molecule YM155, which has shown promising growth inhibitory effects and potent antitumor activities in cell lines and xenograft models, 67,68 is the most well-studied survivin inhibitor. Although the drug's safety and tolerability have been confirmed, single-agent YM155, as monotherapy regimen, demonstrated only limited activity in patients with refractory diffuse large B-cell lymphoma in a phase II clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that YM155 significantly enhanced the antitumor effect of erlotinib in EGFR mutation-positive NSCLC cells with PTEN loss both in vitro and in vivo. YM155, a small-molecule inhibitor of the expression of the antiapoptotic protein survivin, is currently in clinical development as the first survivin suppressant (18,19,(34)(35)(36). This drug was found to exhibit a favorable safety tolerability profile and moderate single-agent activity in a recent phase II trial with patients with advanced, refractory NSCLC (37).…”
Section: Discussionmentioning
confidence: 99%
“…YM155 was identified in a high-throughput screen to identify agents that selectively block survivin promoter activity and is the most clinically advanced of this new class of agents (40). It has demonstrated activity against various tumor types in preclinical studies (19,(40)(41)(42)(43). We selected the VHL null 786-O and the VHL wild-type Caki-1 cell lines as models for our xenograft studies as they both displayed high basal survivin expression.…”
Section: Discussionmentioning
confidence: 99%